Experiências de lutos em idosas no contexto da covid-19 : ateliês artístico-terapêuticos como facilitadores na construção de narrativas - Gusmão, Gisela de Oliveira (2022)
The scope of this research was to know the impacts of complementary therapies in Artistic-Therapeutic Workshops with elderly women affected by grief experiences in the context of the COVID-19 pandemic (Corona Virus Disease 2019), proposing to study the meanings in the coping grief´s process. The secondary objectives aimed to understand the role of minimalist music in the context of contemporary poetics, and its impact on the cultural vision of mourning and death of the participants; to analyze the minimalist aesthetic characteristics present in Qi Gong body practice, in music, and in the Reich's theory of the “seven rings of armor”; to know the benefits of minimalist music as a facilitator in unlocking the “Seven Rings of the Armor”; to analyze the relevance of the social context in the evolution of the participants. The research consisted of an exploratory, descriptive and qualitative study, using the Narrative Research methodology that allows a closer relationship between the researcher and the researched topic, based on Dewey's three-dimensional metaphor concept: temporality; individual and social; and place. As for the procedures, the study provided experiences with minimalist music cradling the practice of Qi Gong - Liu Zi Jue. The survey was carried out with four volunteers aged over 60 years, in fifteen individual, online ArtisticTherapeutic Ateliers, lasting 50 minutes and generating converstions. The narratives produced, as well as the experiences between myself and each one of them, enunciated the general aspects of mourning, the perception of this phenomenon and the strategies used in an attempt to overcome it. The narratives also brought indications of the benefits of these therapies and the approach with Narrative Research, inferring that this methodology contributed to the process of elaboration of the grief experienced and in the revision of the vision regarding the death of the participants, also representing a social contribution to facing the pandemic.